2010
DOI: 10.4055/cios.2010.2.3.130
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cruciate Ligament Reconstruction in Patients with Generalized Joint Laxity

Abstract: Generalized joint laxity is a genetically determined component of overall joint flexibility. The incidence of joint laxity in the overall population is approximately 5% to 20%, and its prevalence is higher in females. Recently it was noticed that individuals with generalized joint laxity are not only prone to anterior cruciate ligament injuries but also have inferior results after a reconstruction. Therefore, an anterior cruciate ligament reconstruction in patients with generalized laxity should be undertaken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 58 publications
1
27
0
Order By: Relevance
“…Assessing Beighton's criteria individually showed the greatest differences between groups for knee hyperextension and thumb apposition (Table ). Based on these findings, both criteria may represent an increased vulnerability to ACL injury, but knee hyperextension is much more frequently described in ACL‐injured patients (Kim et al, ; Myer et al, ; Ramesh et al, ). Knee hyperextension may also occur independently, not as the result of generalized hypermobility.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Assessing Beighton's criteria individually showed the greatest differences between groups for knee hyperextension and thumb apposition (Table ). Based on these findings, both criteria may represent an increased vulnerability to ACL injury, but knee hyperextension is much more frequently described in ACL‐injured patients (Kim et al, ; Myer et al, ; Ramesh et al, ). Knee hyperextension may also occur independently, not as the result of generalized hypermobility.…”
Section: Discussionmentioning
confidence: 99%
“…We found that 58% of injured siblings taking part in this current study had generalized hypermobility. Hypermobility has been reported in 42.6% of patients with ACL injuries (Ramesh et al, ) but only in 5–20% of the general population (Kim et al, ) and is a likely risk factor for ACL injury.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations